A comparison on financial literacy between welfare recipients and non-welfare recipients in Brunei. Issue 7 (13th July 2015) - Pg Md Salleh, Ak Md Hasnol Alwee
Abstract : Purpose: – The purpose of this paper is to provide insights onto the level of financial literacy in Brunei, notably focussing on the findings of welfare recipient's vis-à-vis non-welfare recipients. Design/methodology/approach: – Findings are based on structured interviews with 431 heads of households (215 welfare recipients and 216 non-welfare recipients), within the realm of money management, emergency planning and investing for goals. To analyze the data, Pearson's χ 2 test and logistic regressions are undertaken. Findings: – The findings underline the importance of enhancing the level of financial literacy, notably for low-income households and those in poverty, as the analysis highlighted their level of financial literacy was significantly lower than non-welfare recipients. Research limitations/implications: – Future researches may want to consider a random sampling approach and/or using other districts in the country, to ascertain a representative set of findings. Practical implications: – The implication of the findzings highlights the need for welfare programs to consider incorporating financial literacy programs, designed specifically for welfare recipients, distinct from non-welfare recipients. Originality/value: – There is currently no known research on financial literacy related to Brunei. Further, the paper also focusses on financial literacy, as a means to assist those in welfare or poverty, in order to enhance their financial well-being.